2018
DOI: 10.1002/jlb.mr1117-471r
|View full text |Cite
|
Sign up to set email alerts
|

IL-20 receptor cytokines in autoimmune diseases

Abstract: IL-19, IL-20, and IL-24 are the members of IL-10 family. They are also known as IL-20 receptor (IL-20R) cytokines as they all signal through the IL-20RA/IL-20RB receptor complex; IL-20 and IL-24 (but not IL-19) also signal through the IL-20RB/IL22RA1 receptor complex. Despite their protein structure homology and shared use of receptor complexes, they display distinct biological functions in immune regulation, tissue homeostasis, host defense, and oncogenesis. IL-20R cytokines can be expressed by both immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 69 publications
(151 reference statements)
1
54
1
Order By: Relevance
“…This was consistent with the previous findings, which demonstrated that IL-22 receptor was strictly expressed on the tissue but absent on immune cells (35). Thus, signaling through IL-24 in regulation of T cells was dependent on the expression of IL-20R1/IL-20R2 heterodimeric complex, which was also the receptor for IL-20 (11). Furthermore, since anti-tumor property of IL-24 was dosedependent, we also chose two different concentration (10 ng/ml as low concentration and 100 ng/ml as high concentration) of recombinant IL-24 for stimulation based on the plasma IL-24 level in colorectal adenocarcinoma patients and healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent with the previous findings, which demonstrated that IL-22 receptor was strictly expressed on the tissue but absent on immune cells (35). Thus, signaling through IL-24 in regulation of T cells was dependent on the expression of IL-20R1/IL-20R2 heterodimeric complex, which was also the receptor for IL-20 (11). Furthermore, since anti-tumor property of IL-24 was dosedependent, we also chose two different concentration (10 ng/ml as low concentration and 100 ng/ml as high concentration) of recombinant IL-24 for stimulation based on the plasma IL-24 level in colorectal adenocarcinoma patients and healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Interleukin (IL)-24, which is also called melanoma differentiation associated gene-7, is a IL-20 cytokine family member and is expressed primarily in T cells and marcophages (9,10). IL-24 receptor belongs to type II cytokine receptor family, and consists of two heterodimeric receptor complexes, IL-20R1/IL-20R2 and IL-22R1/IL-20R2 (11). IL-24 is a potential anti-tumor agent and affects a broad array of cancers, which selectively inhibits tumor cell growth, invasion, metastasis, and angiogensis, induces cancer-selective apoptosis, stimulates anti-cancer immune response, sensitizes cancer call to therapies (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained by real-time PCR as well as the proteome profiler showed a significant decrease in its expression and secretion. Although this cytokine is involved in the process of wound healing, the overproduction of IL24 underlies pro-inflammatory autoimmune diseases such as psoriasis, allergic contact dermatitis, atopic dermatitis, rheumatoid arthritis and inflammatory bowel disease [40,41]. Therefore, a decrease in the secretion of IL24 by MSCs as a result of Vadadustat treatment seems to be a beneficial effect when considering the use of Vadadustat preconditioned MSCs in the treatment of patients with autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In each 20 µL reaction 100 ng of cDNA template and 0.5 µM forward and reverse primers was used. PCR reaction was started with two initial steps at 50 • C and 95 • C each for 2 min, followed by 40 Primer pairs for LEP (Cat. no.…”
Section: Gene Expression Analysis By Real-time Pcrmentioning
confidence: 99%
“…IL-24 is a member of IL-10 family of cytokines which signals through the IL-20 receptor. 10 The receptors for IL-24 are mainly expressed on epithelial cells including the colonic mucosa. It is produced by activated immune cells including T and B cells, and has a suppressor effect on Th1 and Th17 cells.…”
Section: Paradoxical Gastrointestinal Effects Of Interleukin-17 Blockersmentioning
confidence: 99%